Sustainable and regional gastronomy: cassava leaves as a potential ingredient for gluten-free biscuits (Research, Society and Development, 2021)
The addition of roots derivatives to bakery products may be a promising alternative to add value to these products. This study aimed to characterize and evaluate the effect of cassava leaves on the properties of gluten-free biscuits (GFB). The ingredients used were cassava flour, rice flour, cuí, tapioca flour, and 0 (F0), 3.69% (F1), 5.34% (F2), and 7.38% (F3) of cassava leaves (CCL). The results were evaluated by analysis of variance, followed by Scott-Knott test (p-value